KEMITRAAN PEMERINTAHAN DALAM PENGEMBANGAN OBJEK WISATA DESA TERINDAH DI NAGARI TUO PARIANGAN KABUPATEN TANAH DATAR SUMATERA BARAT TAHUN 2018-2020 - Aditya Pratama; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Nagari Tuo Pariangan is one of the villages in Tanah Datar Regency. Nagari Tuo Pariangan has various tourist attractions and has been named the most beautiful village in the world by Budget Travel's version so that it becomes a tourist attraction and is visited by many tourists. The wealth and tourism potential of Tanah Datar Regency, of course, requires good and proper management. In developing a tourist village, a partnership between the government and all existingresources is needed to optimize the tourism potential it has. However, the local government has not been optimal in managing Nagari Tuo Pariangan tourism, this can be seen from the absence of a development plan in the form of RIPPDA. This study aims to determine government partnerships and the inhibiting factors of government partnerships in developing the most beautiful village tourism object in Nagari Tuo Pariangan, Tanah Datar Regency. This study uses descriptive qualitative methods and data collection techniques based on observations or observations, interviews, and documentation. The results of this study indicate that the partnership in developing the most beautiful village tourism object in Nagari Tuo Pariangan, Tanah Datar Regency in 2018-2020 has not gone well, this can be seen from the decline in the number of tourists visiting in 2018-2020. The factors that become obstacles in developing the most beautiful village tourism object in Nagari Tuo Pariangan are that the PERDA on RIPPDA 2017-2025 has not been stipulated as a guide for the development of the tourism sector, tourism objects in Nagari Tuo Pariangan are on communal land, there are still limited facilities and infrastructure supporting tourism, the quality and quantity of human resources for managing tourist destinations is still limited, and the creative economy sector has not yet supported tourism. Keywords: Nagari Tuo Pariangan, Government Partnership